DIALECT VARIETIES OF ALAS, GAYO AND KARO: VARIETAS DIALEKTIKA ALAS, GAYO DAN KARO - Wikiaprian Pinim; Saddam Hasrul (Jurnal Pendidikan dan Sastra Inggris, 2022)
This study was aimed to describe the factors of varieties of Alas, Gayo, and Karo dialects in Southeast Aceh province. The focus was on the verb usage in those three dialects. This study was designed qualitatively. The collected data was from the individual interviewee who is the speaker of Gayo, Alas, and Karo. The data consisted of the phonemes/accents and vocabularies from thosethree languages. On the basis of the research findings, the varieties of Alas and Gayo dialect cause by the distance and geographical factor. Whereas the influenced factor that make Alas and Karo dialects are varied is the historical factor where these two languages had been mixed since hundred years ago. Also, the close relationship in those three dialects becomes the factor that triggers the varieties of dialects. In conclusion, the factor of dialect varieties of Alas, Gayo, and Karo are caused by some factors, namely geographical factor, historical factor, and the close relationship among the languages.